2021
DOI: 10.1177/15579883211024375
|View full text |Cite
|
Sign up to set email alerts
|

“I Wanted to Be There as a Father, but I Couldn’t”: A Qualitative Study of Fathers’ Experiences of Postpartum Depression and Their Help-Seeking Behavior

Abstract: Postpartum depression (PPD) is one of the most common mental health problems among new parents. Past studies have examined PPD in women; however, the condition is less understood in men. This study aimed to explore the lived experiences of men or fathers with PPD and to understand the barriers and facilitators of help-seeking among fathers with PPD. Eight fathers with PPD were interviewed and data were subsequently analyzed through interpretative phenomenological analysis. The fathers perceived fatherhood as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…In Spain, Barbeta-Viñas & Cano (2020) identified what they defined as the 'fatigued father' profile in committed fathers who found their own conditions unacceptable for childcare. Similarly in Sweden, Pedersen et al (2021) observed some men committed to childcare to suffer post-partum depression and regret. Hence it is important to verify whether regret is greater among fathers deeply involved in childcare.…”
Section: Intensive Maternity As Ideal and Reproduction Of Role Expect...mentioning
confidence: 92%
“…In Spain, Barbeta-Viñas & Cano (2020) identified what they defined as the 'fatigued father' profile in committed fathers who found their own conditions unacceptable for childcare. Similarly in Sweden, Pedersen et al (2021) observed some men committed to childcare to suffer post-partum depression and regret. Hence it is important to verify whether regret is greater among fathers deeply involved in childcare.…”
Section: Intensive Maternity As Ideal and Reproduction Of Role Expect...mentioning
confidence: 92%
“…Other somatic dysfunction includes loss of appetite, weight loss, less physical activity and poor concentration (Ballard et al, 1994). , 2021), resentment of the infant (Eddy et al, 2019;Pedersen et al, 2021) and less interaction such as communication and physical contact with children (Boyce et al, 2007;Sethna et al, 2015).…”
Section: Somatic Symptomsmentioning
confidence: 99%
“…As a result, they experience unique barriers to initiating help‐seeking and receiving support. Pedersen et al (2021) found that fathers believe PND is a condition which affects mothers, so they may not identify with the illness despite feeling unwell. Mental health literacy for PND in fathers is lower than that for mothers (Swami, Barron et al, 2020a), meaning self‐identification may be limited.…”
Section: Implications For Mental Health Practicementioning
confidence: 99%
“…To destigmatise paternal PND it is important to provide non‐judgmental care to fathers with depression, but the condition is considered “taboo” (Pedersen et al, 2021, p. 6). Stigma around male mental health can be social or self in origin (Covello, 2020): with paternal PND, it is likely both.…”
Section: Implications For Mental Health Practicementioning
confidence: 99%
See 1 more Smart Citation